How can we better support families living with cardiovascular disease and depression?. Issue 1 (14th March 2016) - Jones, Martin; Thompson, David; Ski, Chantal; Clark, Robyn; Gray, Richard; Vallury, Kari; Alam, Ferdous
Abstract : Purpose: – The purpose of this paper is to discuss the role of psychosocial treatments to support families living with cardiovascular disease (CVD) and depression. The paper highlights that depression in people with CVD is a predictor of non-adherence to both medicines and cardiovascular rehabilitation programmes. The authors believe there is a clinical need to develop a programme of care to support the whole family to adhere to cardiovascular rehabilitation programmes. Design/methodology/approach: – A team of expert cardiovascular nurses, mental health nurses (MHN) and cardiologist clinical opinions and experiences. These opinions and experiences were supplemented by literature using MEDLINE as the primary database for papers published between December 2000 and December 2013. Findings: – People with CVD who become depressed are more likely to stop taking their medicine and stop working with their health care worker. Most people with heart and mood problems live with their families. Health workers could have a role in supporting families living with heart and mood problems to their care and treatment. The paper has highlighted the importance of working with families living with heart and mood problems to help them to stick with care and treatment. Originality/value: – Most people with heart and mood problems live with their families. The paper has highlighted the importance of working with families living with heart and mood problems to help them to persevere with care and treatment. MHN may have a role, though consideration should also be given to exploring the role of other health care workers and members of the community. As the population ages, clinicians and communities will need to consider the impact of depression on adherence when working with families living with CVD and depression.